Comparative analysis of upper body postural angles and their association with neck pain in car and motorcycle drivers - Aafreen Aafreen; Abdur Raheem Khan; Ashfaque Khan; Ausaf Ahmad; Monira I. Aldhahi; Weam Okab Alsalem; Mohammed M Alshehri; Almutasim Billa Moafa; Ahmed Ghazwani; Mohammad Abu Shaphe (Transportation Research Interdisciplinary Perspectives)
Purpose: This study aimed to assess upper-body postural angles and neck pain among car drivers and motorcycle drivers separately, and to compare these outcomes between the two groups. Methods: This cross-sectional study comprised a total of 200 participants, with an equal distribution between car drivers (n = 100) and motorcycle drivers (n = 100). To evaluate upper-body postural alignment, measurements of the craniovertebral angle, sagittal head tilt, coronal head tilt, and thoracic flexion angle were obtained.The severity of neck pain was measured using a visual analog scale. The data were analysed to compare the upper-body postural angle and neck pain between driver groups. Result: The study found that car drivers had significantly higher mean craniovertebral angle (CVA) of 52.6 degree (°) compared to 47.2° in motorcycle drivers (p = 0.0001), a lower sagittal head tilt of 10.2° versus 12.3° (p = 0.0001), and a lower thoracic flexion of 26.4° versus 30.7 (p = 0.023). However, motorcycle drivers reported a significantly higher mean neck pain score of 6.1, compared to 5.5 in car drivers (p = 0.0001). Thus, the prevalence of neck pain was higher in motorcycle driver (54 %) compared to 36 % in car drivers. Conclusion: This study found that both car and motorcycle drivers had distinct upper-body postural angles and neck pain levels. When comparing the two groups, motorcycle drivers showed greater deviations in craniovertebral and thoracic flexion angles and a higher prevalence of neck pain than car drivers. These results highlight the need for targeted interventions to address neck health in both populations.